Influence of the Culture Conditions on Camellia sinensis Cell Cultures - Esteban-Campos, Pilar; Vela, Pilar; Rodríguez-Solana, Raquel; López-Sánchez, José Ignacio; Salinero, Carmen; Pérez-Santín, Efrén (Foods, 2025)
Since the last century, it has been shown that dedifferentiated cells of Camellia sinensis can produce catechins and other secondary metabolites under in vitro conditions, with potential applications in the cosmetic, pharmaceutical and food industries. In this work, cell suspension cultures of a C. sinensis cell line (LSC-5Y) were established in a liquid medium in order to optimize the biomass productivity, catechin monomer (GC, EGC, C, EC, CG, and ECG) and alkaloid (TB and CAF) productivity. The following factors were evaluated: concentration of growth regulators (BA and IBA), inoculum size, age of the cell line, light exposure, and effect of biotic elicitors (MeJA and extracts of Ciborinia camelliae). GC, EGC, and ECG increased approximately 1.80-fold when the auxin IBA concentration was increased from 0.1 to 2.0 mg/L. In addition, better productivity of EGC, C, EC, and CAF was achieved by using inoculum densities between 50 and 100 g/L. Although lower inoculum densities (25 g/L) showed a higher growth rate (0.20 d−1), the use of inoculum densities higher than 25 g/L favors a 2–4-fold increase in total catechin (TC) productivity, with maximum productivity being reached after 21 days of culture. However, the cell line showed instability in TC productivity: in the short term (in three successive subcultures), the coefficient of variation was 32.80%, and catechin production capacity was 2.5 years with maximum productivity at 0.5 years. Finally, it was observed that ethanol, used as an elicitor solvent, has a strong elicitor effect capable of increasing the accumulation of catechins up to 5.24 times compared to the treatment without an elicitor.
Keywords: Camellia sinensis cell culture; tea; catechins; biomass productivity; elicitors; growth regulators